2010
DOI: 10.4025/actasciagron.v32i3.2166
|View full text |Cite
|
Sign up to set email alerts
|

Uso de agentes microbianos e químico para o controle de Meloidogyne incognita em soja

Abstract: RESUMO.Nematoides de galhas constituem importante grupo de patógenos da cultura da soja e o manejo integrado é uma das principais medidas de controle que visam à redução de perdas econômicas. Neste trabalho foi avaliada a eficácia dos fungos Paecilomyces lilacinus (Thom.) Samsom e Pochonia chlamydosporia (Goddard) Zare & Gams (sinonímia Verticillium chlamydosporium), de um produto comercial à base de Bacillus sp. (Nemix) e do nematicida químico Aldicarb no controle de Meloidogyne incognita em soja, variedade M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 15 publications
1
5
0
4
Order By: Relevance
“…Therefore, this genus performs two important functions to ecosystem: wood decomposition and pests control (Mankau, 1980). Further, saprophytic ability turns biological agents into a promising control strategy (Nunes et al, 2010) and nematode trapping fungi present no specificity to host so any nematode in soil can be preyed by them (Askary, 2015). Koziak et al (2007) confirm that Nematoctonus genus are found in agricultural soils and contains predators and parasitoids species, unlike other nematophagous genus that generally contemplates only one control profile.…”
Section: Introductionmentioning
confidence: 61%
“…Therefore, this genus performs two important functions to ecosystem: wood decomposition and pests control (Mankau, 1980). Further, saprophytic ability turns biological agents into a promising control strategy (Nunes et al, 2010) and nematode trapping fungi present no specificity to host so any nematode in soil can be preyed by them (Askary, 2015). Koziak et al (2007) confirm that Nematoctonus genus are found in agricultural soils and contains predators and parasitoids species, unlike other nematophagous genus that generally contemplates only one control profile.…”
Section: Introductionmentioning
confidence: 61%
“…Likewise, AL-HAZMI; TARIQJAVEED (2016) checked different performances among species, justified by pathogenic ability of the isolates or their origin. By analyzing the reduction percentual of galls and egg masses of M. javanica (Tables 3 and 4), it was verified that H. mastrucata, H. portegna and H. petaloides presented control potential superior to many commercial products of antagonists, such as Rizotec in cucumber (VIGGIANO et al, 2014), Rizotec and Onix SC + Quality WG in tomato (CARVALHO, 2017), Nemix TS in soybean (NUNES et al, 2010), Trichodermil SC 1306and Quality in bean (AGUIAR et al, 2014, revealing the potential for commercial use, especially remembering that these results were obtained with low dosage of inocula.…”
Section: Discussionmentioning
confidence: 94%
“…Researches on biocontrol of nematodes generally consider the introduction of the antagonist agent before transplanting the plant host (DALLEMOLE-GIARETTA et al, 2008;AL-HAZMI;TARIQJAVEED, 2016), resulting in a longer interaction to reduce nematode inoculum. It is an advantage for ovicidal antagonists, such as Trichoderma (SZABÓ et al, 2012) and Pochonia chlamydosporia (NUNES et al, 2010). In this study, fungi were added during sowing, having 19 days to establish in the substrate and roots before the addition of M. javanica.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Geralmente, são classificados segundo seu hábito nutricional. Dentre os grandes grupos de nematoides estão os fitonematoides, ou nematoides parasitas de plantas, que causam perdas econômicas significativas em uma grande variedade de culturas (Nunes et al, 2010).…”
Section: Introductionunclassified